2016
DOI: 10.1155/2016/4592346
|View full text |Cite|
|
Sign up to set email alerts
|

4-Phenylbutyric Acid Attenuates Pancreatic Beta-Cell Injury in Rats with Experimental Severe Acute Pancreatitis

Abstract: Endoplasmic reticulum (ER) stress is a particular process with an imbalance of homeostasis, which plays an important role in pancreatitis, but little is known about how ER stress is implicated in severe acute pancreatitis (SAP) induced pancreatic beta-cell injury. To investigate the effect of 4-phenylbutyric acid (4-PBA) on the beta-cell injury following SAP and the underlying mechanism, twenty-four Sprague-Dawley rats were randomly divided into sham-operation (SO) group, SAP model group, and 4-PBA treatment g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…16,17 Many studies implicated ER stress in the pathogenesis of various diseases and demonstrated the therapeutic potential of 4-PBA by using it as a reducer of ER stress. 3,[18][19][20] In the present study, we showed that the expression of ER stress markers was significantly enhanced in IL-1β-stimulated RASFSs, which is consistent with previous reports 9,21 and indicates that ER stress is implicated in the pathogenesis of RA. RASFSs treated with 4-PBA had significantly lower levels of ER stress indicators, which means that 4-PBA reduces ER stress in these cells.…”
Section: Discussionsupporting
confidence: 93%
“…16,17 Many studies implicated ER stress in the pathogenesis of various diseases and demonstrated the therapeutic potential of 4-PBA by using it as a reducer of ER stress. 3,[18][19][20] In the present study, we showed that the expression of ER stress markers was significantly enhanced in IL-1β-stimulated RASFSs, which is consistent with previous reports 9,21 and indicates that ER stress is implicated in the pathogenesis of RA. RASFSs treated with 4-PBA had significantly lower levels of ER stress indicators, which means that 4-PBA reduces ER stress in these cells.…”
Section: Discussionsupporting
confidence: 93%
“…Acute pancreatitis (AP) is characterized by local pancreatic inflammation that frequently affects peripancreatic tissues or remote organs and leads to systemic inflammatory response syndrome (SIRS) and multiple organ dysfunction syndrome, and~20 -30% of all patients progress to severe AP, which has a high mortality rate because of complications (33). Previous study has shown that ERS was involved in AP and associated acinar and ␤-cell injury (11,35), as well as damage of the lung (24). 4-Phenylbutyric acid (4-PBA) has three main pharmacological effects as an ammonia scavenger (14), a weak histone deacetylase inhibitor (16), and an ER stress inhibitor (31).…”
Section: Introductionmentioning
confidence: 99%
“…In the article titled “4-Phenylbutyric Acid Attenuates Pancreatic Beta-Cell Injury in Rats with Experimental Severe Acute Pancreatitis” [ 1 ], the authors made a mistake in the process of analysis by using the recommended concentrations of reference standard which should be diluted by 20 times to be the actual concentrations.…”
mentioning
confidence: 99%